ENHANCING STUDENTS’ MOTIVATION IN ENGLISH LANGUAGE LEARNING THROUGH GAMIFICATION - Naviantara, Denta; Suwartono, Tono; Romdona, Yaomal (Jurnal PTK dan Pendidikan, 2023)
One of the contributing factors to the students' limited English proficiency can be attributed to the teacher's insufficient emphasis on fostering students’ motivation throughout the learning journey. The purpose of this research is to identify the initial factors influencing students' motivation to learn English, as well as to investigate the potential of gamification in increasing their motivation to study the language. The current study is a class action research that was carried out in the 8th grade of State Junior High School 1 Banyumas during the academic year 2023/2024. A dataset of observations and questionnaires administered to a cohort of 35 students is used in the study. The application of descriptive statistics is used in the data analysis process. According to research, engagement levels increased from pre-research (62% observation sheet, 68.21% questionnaire) to post-research (71.62% observation sheet, 79.36% questionnaire). Gamification has a positive impact on learners’ motivation because it increases interactivity and enjoyment in the learning environment. Hence, gamification can be a viable approach to increasing learners' motivation to acquire English language proficiency.